Influence of Phase Change Material in High-Performance Concrete - V., Naveenraj; K. C., Denesh; S. K., Gowtham (International Journal of Scientific Research in Civil Engineering, 2016)
Curing of concrete is maintaining moisture in the concrete during early ages specifically within 28 days of placing concrete, to develop desired properties. Curing concrete plays a major role in developing the concrete microstructure and pore structure. Good curing is not always practical in many cases. In case of High performance concrete (HPC) at low water cement ratio, the curing plays an important role in developing the strength of concrete. Improper or insufficient curing leads to a reduction in the strength of the concrete to a great extent. Concept of self curing is to reduce the water evaporation from concrete and hence increase the water retention capacity of the concrete compared to conventional concrete. Improper curing can easily cut the strength of concrete. Curing simply means keeping the water in the concrete where it can do its job of chemically combining with the cement to change the cement into tough glue that will help to develop strong durable concrete. Good curing means keeping concrete damp and at about 70 o F until the concrete is strong enough to do its job. The focus of this study is on the benefits of internal curing for pavement. Because concrete pavements have large surface to volume ratios and are exposed to the environment, it is particularly difficult to achieve proper curing. However, proper curing of pavements is important because it reduces early age cracking tendencies and improves concrete strength and performance. The aim of the study is to produce a properly cured and durable concrete and to study the mechanical properties of concrete. This paper shows how Super Absorbent Polymer (SAP) influences concrete properties, by comparing the results of concrete mixes with SAP and controlled concrete without SAP.